Analysis of Factors Affecting Childbirth with Caesarean in Kediri, Indonesia - Rahmawati, Dian; Tamtomo, Didik; Budihastuti, Uki Retno (Journal of Maternal and Child Health, 2016)
Background: Cesarean section has a maternal mortality risk 4 times higher than those with normal birth. In Kediri, the incidence of cesarean section increased, i.e. 8.5% in 2012 to 15.3% in 2015. Therefore, this study aimed to analyze the factors affecting cesarean section deliveries in Kediri.Subjects and Method: This was an observational analytical study with case control design. A total sample of 50 women giving birth with cesarean section and 50 normal birth. The population was all women giving birth by cesarean section in Kediri. A sampling technique was using a Fixed Sampling Disease. Data analysis used multiple logistic regression.Results: Maternal age <20 or Ã¢â°Â¥35 years was lower the chances of having cesarean 0.83 times compared to mothers aged 20-35 years and was not statistically significant (OR = 0.83; 95% CI = 0:26 to 2.78, p = 0.757), Parity 1 and Ã¢â°Â¥4 increase of 1.64 times more likely to undergo cesarean section than parity 2-3 and was not statistically significant (OR = 1.64; 95% CI = 0.60 to 4:58, p=0341). Less physical activity during pregnancy increases the likelihood of cesarean section 1:10 of times and was not statistically significant (OR = 1:10; CI 95% = 0:38 to 2.90, p = 0932). Mothers who experienced complications during labor increases the risk 12 times through cesarean section and was statistically significant (OR = 12; 95% CI = 3.56 to 41.81, p <0.001). Mothers who do their own request for delivery by cesarean section increases the likelihood 21 times through cesarean section and was statistically significant (OR = 21:24; 95% CI = 5.22 to 86.33, p <0.001).Conclusion: There is a positive correlation, very strong and statistically significant between the complications of labor and delivery at hisown request by cesarean section.Keywords: cesarean section, affecting factorsCorrespondence:ÃÂ Dian Rahmawati. School of Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: lintangkayana31@gmail.com.Journal of Maternal and Child Health (2016), 1(1): 34-40https://doi.org/10.26911/thejmch.2016.01.01.06